Pulmonary Embolism and Heart Failure: A Reappraisal - Mattia Arrigo; Lars Christian Huber (Cardiac Failure Review)
Acute heart failure and acute pulmonary embolism share many features, including epidemiological aspects, clinical presentation, risk factors and pathobiological mechanisms. As such, it is not surprising that diagnosis and management of these common conditions might be challenging for the treating physician, in particular when both are concomitantly present. While helpful guidelines have been elaborated for both acute heart failure and pulmonary embolism, not many studies have been published on the coexistence of these diseases. With a special focus on diagnostic tools and therapeutic options, the authors review the available literature and, when evidence is lacking, present their own approach to the management of dyspnoeic patients with acute heart failure and pulmonary embolism.